Effect of Phosphatidylcholine Unsaturation on the Lateral Segregation of Palmitoyl Ceramide and Palmitoyl Dihydroceramide in Bilayer Membranes - Al Sazzad, Md Abdullah (Langmuir : the ACS journal of surfaces and colloids, 2016)
To better understand the interactions of saturated ceramides with unsaturated glycerophospholipids in bilayer membranes, we measured how palmitoyl ceramide (PCer) and dihydroceramide (dihydro-PCer, lacking the trans 4 double bond of the sphingoid base of ceramide) can interact with phosphatidylcholines (PCs) with palmitic acid in the sn-1 position and increasingly unsaturated acyl chains in the sn-2 position. The PCs were 16:0/18:1 (POPC), 16:0/18:2 (PLPC), 16:0/20:4 (PAPC), and 16:0(22:6 (PDPC). We also included di-18:1-PC (DOPC) to compare it with POPC. Because the ceramides were expected to segregate laterally to an ordered ceramide-rich phase, we determined the formation of the ordered phase using lifetime analysis of trans-parinaric acid (tPA) fluorescence. The presence of ordered domains, as indicated by tPA lifetime analysis, was verified by an analysis of tPA anisotropy as a function of temperature. The interaction between PCer and POPC was clearly more favored than interactions with DOPC, as seen from a more thermostable gel phase in POPC than in DOPC at equal ceramide content. The concentration needed for PCer gel phase formation was also lower in POPC than in the DOPC bilayers, suggesting that POPC had better miscibility in the ordered phase. The increased unsaturation of the sn-2 acyl chains of the PCs had more clear effects of dihydro-PCer segregation than on PCer segregation, and the dihydro-PCer gel phase became more thermostable as the unsaturation in the PC increased. We conclude that the interactions between ceramides and PCs were complex and affected both by the trans 4 double bond of PCer by the palmitoyl acyl in the sn-1 position and by the overall degree of unsaturation of the sn-2 acyl chain of the PCs